Features of the of psoriatic arthritis course in patients with hyperuricemia or gout - O.P. Bortkevych; D.M. Sydorenko; O.I. Mitchenko; L.H. Voronkov; A.S. Krylova (Bolʹ, Sustavy, Pozvonočnik)
Background. Recent studies indicate a possible link between elevated uric acid levels and a more severe course of psoriatic arthritis (PsA), in particular, more frequent development of erosive changes. The purpose was to determine the clinical, laboratory, and radiological features of PsA in patients with hyperuricemia or gout. Materials and methods. A retrospective analysis of the medical records of 98 patients with PsA, which were divided into groups based on normo/hyperuricemia/presence of gout and type of suppurative therapy. The following parameters were analyzed: general clinical, laboratory (determination of inflammatory markers, urea level), and instrumental (X-ray examination) parameters. Methods of questionnaire and biomedical statistics were used. Results. Compared with patients with normouricemia, the hyperuricemic group was more often male (73 vs. 89 %). The number of enthesitis (anamnestic) was higher in the hyperuricemic group than in the normouricemic group (41 vs. 23 %, p = 0.04). In the first group, the erythrocyte sedimentation rate (ESR) did not exceed the normal range and was 9.00 (IQR 5.0–15.0) mm/h, in the second group it was higher (12.00 (IQR 5.0–21.5) mm/h), although statistically insignificant. The level of C-reactive protein (CRP) was statistically higher in the hyperuricemia group. Patients with gout had higher values of uric acid (median — 549.0 mmol/l), ESR (median – 16.0 mm/h) and CRP (median — 11.35 mg/l). In the hyperuricemia group, the highest radiological stage was diagnosed more often. The significant lower level of uric acid (281.0 (IQR 223.0–336.0) mmol/l) was observed in the combined group of biological and combined therapy (p = 0.049) compared with synthetic therapy. Conclusion. Patients with PsA had a frequent comorbidity with hyperuricemia and gout (30 %), which influenced the more severe course of the disease, more enthesitis, higher radiological stage and inflammation levels, which should be considered in patient management.